Pengaruh Pengungkapan Corporate Social Responsibility Dan Pengungkapan Good Corporate Governance Terhadap Nilai Perusahaan dengan Kinerja Keuangan Sebagai Variabel Moderasi - Ismi Dwi Atikah; Etty Gurendrawati; Muhammad Yusuf (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to demonstrate the effect of Corporate Social Responsibility (CSR) disclosure and Good Corporate Governance (GCG) disclosure on company value with financial performance as a moderating variable. The research method used is a quantitative approach with the unit of analysis being companies in the banking sub-sector listed on the Indonesia Stock Exchange (IDX) during the period 2021-2024. The sample selection method used purposive sampling, resulting in 25 sample companies with a total of 100 data observations. The analysis technique in this study used descriptive statistical analysis and panel data regression analysis with the Eviews 13 application. The tests conducted included panel data regression model testing, classical assumption testing, partial testing, simultaneous testing, coefficient of determination testing, and Moderated Regression Analysis (MRA) testing. The results of this study indicate that CSR disclosure has a positive effect on company value, GCG disclosure has no effect on company value, financial performance has no effect on company value, financial performance is unable to moderate the effect of CSR disclosure on company value, and financial performance is unable to moderate the effect of GCG disclosure on company value. Future research should expand the sample size, extend the observation period, and add other variables such as government policy, macroeconomic conditions, and specific industry characteristics. In addition, future research could use more comprehensive GCG indicators and other financial performance proxies that are more sensitive to company value.